2010
DOI: 10.1074/jbc.m109.057455
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Gating Motif and C-type Inactivation in Prokaryotic Voltage-gated Sodium Channels

Abstract: Prokaryotic voltage-gated sodium channels (Na V s) are homotetramers and are thought to inactivate through a single mechanism, named C-type inactivation. Here we report the voltage dependence and inactivation rate of the NaChBac channel from Bacillus halodurans, the first identified prokaryotic Na V , as well as of three new homologues cloned from Bacillus licheniformis (Na V BacL), Shewanella putrefaciens (Na V SheP), and Roseobacter denitrificans (Na V RosD). We found that, although activated by a lower memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 41 publications
3
73
0
Order By: Relevance
“…Mutation of residues in the lower half of S6 can affect the rate of inactivation (29,34), suggesting that this segment is implicated in inactivation. Furthermore, the S4-S5/S6 interface has been implicated as an inhibitory general anesthetic interaction region in K + channels (41).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Mutation of residues in the lower half of S6 can affect the rate of inactivation (29,34), suggesting that this segment is implicated in inactivation. Furthermore, the S4-S5/S6 interface has been implicated as an inhibitory general anesthetic interaction region in K + channels (41).…”
Section: Significancementioning
confidence: 99%
“…Although crystal structures are not yet reported, the bacterial Na + channel NaChBac has been extensively characterized by electrophysiology (22,(28)(29)(30)(31)(32)(33)(34)(35)(36). Additionally NaChBac exhibits conserved slow open channel block in response to local and general anesthetic agents (15, 37).…”
mentioning
confidence: 99%
“…The sodium channel from Bacillus halodurans (NaChBac), the first bacterial sodium channel to be identified, has been well-characterized with respect to its conductance properties (4). Since then a large number of other members of the prokaryotic voltage-gated sodium channel family have been identified and shown to be close sequence and structural homologs (5,6). Several crystal structures of bacterial sodium channels have been published recently (7)(8)(9)(10); in these, the proteins are present in different functional states.…”
mentioning
confidence: 99%
“…However, in 2001 Ren et al (13) isolated NaChBac, a simple prokaryotic sodium channel from Bacillus halodurans that, like potassium channels, but unlike eukaryotic sodium channels, is composed of a single 6TM domain. Subsequently, many more close homologues from both gram-positive and gram-negative sources have been identified (14)(15)(16). In NaChBac, it has been shown that, as predicted, four monomers assemble to form an active channel (17).…”
mentioning
confidence: 99%